Postoperative Functional and Radiological Outcome Comparison of Computer-assisted and Conventional Total Knee Arthroplasty at 6 Months Follow-up: A Cross Sectional Study - Muhammad Budimansyah; Ismail Hadisoebroto Dilogo; Endrotomo Sumargono (The Hip and Knee Journal, 2020)
Background. Computer-assisted navigation TKA has just been adapted in Indonesia for the last decade. The method is aiming to achieve more precise mechanical alignment in TKA. However, controversies still exist especially in terms of functional outcome and radiological outcome.Method. Fifty elderly patients aged more than 50 years old with severe knee osteoarthritis (Kellgren Lawrence stage III or IV) who scheduled for TKA surgery in the first half of 2019 were consecutively sampled. All patients were measured for objective functional status with Western Ontario Mac Master University Index (WOMAC) and Oxford Knee Score (OKS). Weight-bearing, long-leg follow-up radiographs of both lower limbs were taken, and coronal tibiofemoral angle (CTFA), coronal femoral component angle (CFCA) and coronal tibial component angle (CTCA) were measured.Results. Group of computer-assisted navigation TKA surgery was found to have significantly lower WOMAC score (p0.05) and higher OKS score (p0.05). Although not statistically significant, greater angle of deviation is observed in the conventional TKA surgery group. Proportions with deviation of less than 3º were found more in the group using computer navigation.Discussion. The results of this study indicate the advantage of using a computer assisted  system in TKA procedure, in terms of better functional outcome. However, our study only measures mechanical alignment from coronal plane and short term follow up time. Other parameter measurement, such as mechanical alignment on sagittal plane, rotational alignment, and soft tissue balance are also important to determine the success rate of TKA procedure.Conclusion. Patients who had TKA surgery under computer-assisted navigation would benefit a better functional outcome if compared with conventional TKA surgery, as measured with WOMAC and OKS. However, there is no significant difference in terms of radiographic value of coronal-plane mechanical deviation on both methods.